Identification and potential use of RAPD markers linked to yam mosaic virus resistance in white yam (Dioscorea rotundata) - Mignouna, Hodeba D.; Abang, Mathew M.; Onasanya, A.; Agindotan, B.; Asiedu, Robert (2002)
Resistance to Yam mosaic virus (YMV) in tetraploid white yam (Dioscorea rotundata) is inherited differentially as a dominant and recessive character. Elite D. rotundata breeding lines with durable resistance to YMV can be developed by pyramiding major dominant and recessive genes using marker assisted selection (MAS). The tetraploid breeding line, TDr 89/01444, is a source of dominant genetic resistance to yam mosaic disease. Bulked segregant analysis was used to search for random amplified polymorphic DNA (RAPD) markers linked to YMV resistance in F1 progeny derived from a cross between TDr 89/01444 and the susceptible female parent, TDr 87/00571. The F1 progeny segregated 1:1 (resistant: susceptible) when inoculated with a Nigerian isolate of YMV, confirming that resistance to YMV in TDr 89/01444 was dominantly inherited. A single locus that contributes to YMV resistance in TDr 89/01444 was identified and tentatively named Ymv-1. Two RAPD markers closely linked in coupling phase with Ymv-1 were identified, both of which were mapped on the same linkage group: OPW18850 (3.0 centiMorgans [cM]) and OPX15850 (2.0 cM). Both markers successfully identified Ymv-1 in resistant genotypes among 12 D. rotundata varieties and in resistant F1 individuals from the cross TDr 93-1 ´ TDr 87/ 00211, indicating their potential for use in marker-assisted selection. OPW18850 and OPX15850 are the first DNA markers for YMV resistance and represent a starting point in the use of molecular markers to assist breeding for resistance to YMV.